Prevalence of Astigmatism in School Going Children - Naeem Rustam, Rida Ijaz, Hijab Ijaz (Pakistan Journal of Ophthalmology, 2017)
Purpose: To assess the prevalence of astigmatism, and most common type of astigmatism among school going children. Study Design: Cross sectional observational study. Place and Duration of Study: City District Govt. Girls High School, Shadman and “Department of Ophthalmology” FMH College of Medicine & Dentistry, Shadman Lahore from September 2014to February 2015. Materials and Methods: After taking consent data was collected through a self-design performa at City District Govt. Girls High School, Shadman Lahore from 550 students. Each eye was considered as a separate individual data. Total 1098 eyes were taken for the study, age ranges 5 – 16 years. First visual acuity was measured monocularly by using snellen’s visual acuity chart. In case of substandard vision, pinhole test was done to assess the maximum improvement after correction. Amount and type of astigmatism was assessed by using cycloplegic refraction. Eyes with amblyopia, strabismus or other ocular pathologies were excluded. Result: We examined 1098 eyes of the 550 students, with mean age of 10.31 ± 3.276 years including 255 (46.4%) male students and 295 (53.6%) female students. Astigmatism was seen in 818 eyes (74.5%), out of which 0.5 – 1.00 diopter cylinder was the most common and was present in 454 eyes (41.3%), With the rule astigmatism was seen in 605 eyes (55.1%) and 355 (32.3%) had compound myopic astigmatism. Conclusion: With the rule astigmatism and compound myopic astigmatism are more common among males and females and maximum in the age group of 14 – 16 years of age. Key words: Amblyopia, Astigmatism, Children, Refractive error.